PENYALAHGUNAAN POSISI DOMINAN OLEH GOOGLE DALAM SISTEM PEMBAYARAN APLIKASI DI INDONESIA - Hutabarat, Sylvana Murni Deborah; Muhammad Syahrul Ramadhan (Faculty of Law, University of Mataram, 2025)
The development of the digital economy in Indonesia has reinforced Google’s dominance through the Google Play Store as the primary platform for application distribution among Android users. Google’s policy mandating the use of the Google Play Billing System (GPBS), with service fees of up to 30%, has raised significant legal and economic concerns. This study analyzes Google’s dominance within Indonesia’s application ecosystem under Law No. 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition. Employing a normative juridical method, this research adopts statutory, conceptual, and case-based approaches to evaluate whether Google’s policy constitutes an abuse of dominant position. The findings reveal that with a market share exceeding 90%, Google satisfies the criteria for a dominant position as stipulated in Article 25 of Law No. 5 of 1999. The restriction of alternative payment systems and imposition of high service fees potentially hinder competition and harm local application developers. The decision by the Indonesian Competition Commission (KPPU) to sanction Google reflects an effort to enforce the law and foster a fairer digital ecosystem in Indonesia.